Under the sun - Dorros, Arthur (New York Amulet Books, 2004)
Chronicles the harrowing journey of Ehmet, a thirteen-year-old boy from Sarajevo who gets caught up in the ethnic conflicts in the former Yugoslavia. Best-selling and award-winning picture-book writer Arthur Dorros has written his first novel, a thrilling My Side of the Mountain-type survival story. Separated from his parents by the Balkan war, 13-year-old Ehmet must use all his skills to survive a four-hundred-mile journey across wilderness and war-torn landscape to find a place he’s only heard rumors of, a village of children living cooperatively and peacefully away from the violence that is tearing their country apart. He makes shelters, tracks animals, fishes with a thorn, whittles a toothbrush, and collects wild mushrooms when there’s no other food. Under the Sun is an inspiring journey by a master storyteller, created through extensive research and based on actual places.
Keywords: Criticism and interpretation; Yugoslav War, 1991-1995 -- Juvenile fiction; Yugoslav War, 1991-1995 -- Fiction -- Therapeutic use; Bosnia and Hercegovina -- Fiction -- History -- 1992-; Prejudices -- Fiction; Văn học Mĩ; Chiến tranh